The Influence of Self-Efficacy on IPAS Literacy Skills Reviewed from Students' Achievement Motivation - Paulus Raja; Muhammad Arsyad; Kaharuddin Arafah (Postgraduate, University of Mataram, 2025)
IPAS literacy is an essential skill for students to understand and apply natural and social science concepts in daily life. Psychological factors such as self-efficacy and achievement motivation play a crucial role in enhancing students' IPAS literacy skills. This study employs a quantitative approach to investigate the influence of self-efficacy on IPAS literacy skills through achievement motivation among fifth-grade students of Frater Bakti Luhur Elementary School in Makassar for the 2024/2025 academic year. The independent variable in this study is self-efficacy, the intervening variable is achievement motivation, and the dependent variable is IPAS literacy skills. The population consists of all fifth-grade students of Frater Bakti Luhur Elementary School, totaling four classes. One class was designated as the pilot class (36 students), while the remaining three classes served as the research sample, comprising 108 students. Data were collected using a self-efficacy questionnaire, an achievement motivation questionnaire, and an IPAS literacy skills test. This study adopts a causative research design to analyze the relationship between two or more variables, both directly and indirectly. The data analysis technique used is path analysis with a path field model. The analysis results indicate that the IPAS literacy skills and achievement motivation of fifth-grade students are categorized as moderate, while self-efficacy is categorized as low. The path analysis results show that: 1) Self-efficacy has a direct positive and significant influence on students' IPAS literacy skills with a coefficient of 0.142. 2) Achievement motivation has a direct positive and significant influence on students' IPAS literacy skills with a coefficient of 0.145. 3) Self-efficacy has a direct positive and significant influence on students' achievement motivation with a coefficient of 0.358. 4) Self-efficacy has an indirect positive and significant influence on IPAS literacy skills through achievement motivation with a coefficient of 0.016.